Dampak Youtube Pada Kegiatan Belajar Daring Anak Usia Dini di Tengah Pandemi Covid-19 - Dea Ramadhan Putri; Siti Nursanti; Luluatu Nayiroh (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2021)
ABSTRACTThe purpose of this research is to know the impact of YouTube on early childhood online learning activities during the pandemic. The method used in this research is the quantitative method by testing New Media Theory as applied theory. This research subject used early childhood as a research subject at Islam Insan Taqwa Kindergarten as one of the kindergarten schools that uses an online learning system through YouTube. The results obtained from this study are YouTube has a positive impact on early childhood online learning activities amid the pandemic Covid-19. Aspects of the positive impact are knowledge, comfort, innovation, and practice. The increase in new technology knowledge in early childhood in online learning activities got the highest results by 60%. The highest result from the convenience obtained when carrying out online learning activities at home by 42%. Online learning through YouTube is new or innovative for children with the result of 54%. The result of online learning practices that become the response of early childhood in carrying out online learning activities by 70%.Keywords: YouTube, Online Learning, New Media